Current viroid status in Thailand - Tangkanchanapas, Parichate; Reanwarakorn, Kanungnit; Höfte, Monica; Jonghe, Kris De (Agriculture and Natural Resources, 2024)
Importance of the work: Since 2001, several viroids have been found and identified in Thailand in a wide range of economically important crops. However, there has not yet been any complete and up-to-date information published on the status of all viroids in Thailand. Objectives: To provide current and comprehensive information on viroid status, epidemiology and economic impact in Thailand. Results: Since 2001, four pospiviroids (chrysanthemum stunt viroid, citrus exocortis viroid, columnea latent viroid and pepper chat fruit viroid), one hostuviroid (hop stunt viroid), two apscaviroids (grapevine yellow speckle viroid 1 and 2) and one pelamoviroid (chrysanthemum chlorotic mottle viroid) have been found in Thailand. Main finding: This review provided current, complete and up-to-date information on the status of all viroids in Thailand, never before compiled and published, particularly since most early reports are unavailable online.